Digital coaching and its potential to support the return-to-work-process for individuals with chronic musculoskeletal pain - A focus group study - Vedrana Bolic Baric; Gunilla Liedberg; Hanna Lundell; Mathilda Björk; Christina Turesson (Digital Health)
Background Given the growing digitalization of healthcare and society, it becomes crucial to explore whether digital interactions with healthcare professionals, such as coaching, can offer effective support and contribute to an improved return-to-work process and a sustainable work environment for individuals with chronic musculoskeletal pain. Aim To explore perceptions of digital coaching and its potential to support the return-to-work process for individuals with chronic musculoskeletal pain. Methods Three focus group interviews consisting of 14 people—11 women and three men (with a mean age of 48 years)—were conducted. All participants had a goal of returning to work and had completed an interprofessional rehabilitation program due to chronic musculoskeletal pain. Data were analyzed using thematic analysis. Results Findings show that integrating a coach into digital tools could offer new opportunities for personalized guidance, support and feedback to individuals during the return-to-work process. The first theme emphasizes the importance of sustained support throughout the entire return-to-work process—from rehabilitation programs to workforce integration. The second theme outlines the specific tasks and functions expected from a digital coach, as perceived by the participants. Lastly, the third theme explores the envisioned future evolution of digital coaching in chronic musculoskeletal pain management. Conclusions Digital coaching offers promise in addressing challenges during the return-to-work process, acting as a bridge among stakeholders to ensure accessibility, continuity and coordination in rehabilitation and return-to-work efforts.